Business Basics for Musicians: The Complete Handbook from Start to Success - Borg, Bobby (Rowman & Littlefield Publishers, 2020)
Today, when artists are empowered to take greater control of their careers and earnings, the need for musicians to understand the business of music has never been greater. In a digital age overflowing with confusing and ever-changing information, musicians need trusted business advice from a veteran artist who can break down the basics in language they understand. Written by a professional musician for other musicians, Business Basics for Musicians is the laypersons guide to the music industry. In this must-have manual, music industry veteran Bobby Borg presents vital info in a conversational tone and an easy-to-scan format regarding five vital areas that musicians need to succeed: Career Execution, Business Relationships, Pro Teams, Deals and Dollars, and Future Predictions. Everything from copyrights to record deals, to managers, to merchandising, to doing it yourself is covered. With pro interviews, anecdotes, and review quizzes, Business Basics for Musicians is the complete handbook from start to success. Updates for this edition: Changes in copyright laws Summary of the Music Modernization Act Updates on record, merch, publishing, and live performance deals New trends in sponsorships and partnerships with product brands New interviews with industry professionals, including managers, producers, and agents New stories paralleling current events and industry happenings Updated business resources, industry contacts, and URLs